Isolation and identification of a novel phage targeting clinical multidrug-resistant Corynebacterium striatum isolates - Wang, Jiao; Zhang, Meng; Pei, Jiao; Yi, Wei; Fan, Li; Wang, Chunhua; Xiao, Xiao (Frontiers in Cellular and Infection Microbiology, 2024)
Over the past decade, Corynebacterium striatum (C. striatum), an emerging multidrug-resistant (MDR) pathogen, has significantly challenged healthcare settings, especially affecting those with weakened immune systems. Addressing these superbugs requires innovative solutions. This study aimed at isolating and characterizing bacteriophages targeting MDR-C. striatum. Utilizing 54 MDR-C. striatum isolates from a local hospital as target strains, samples were collected from restroom puddles for phage screening using Dot Plaque and Double-layer plate Assays. A novel temperate bacteriophage, named CSP1, was identified through a series of procedures including purification, genome extraction, sequencing, and one-step growth curves. CSP1, characterized by a 39,752 base pair circular double-stranded DNA genome with HK97-like structural proteins and potential for site-specific recombination, represents a new species within the unclassified Caudoviricetes class. This was further supported by transmission electron microscopy, genomic evolutionary analysis, and collinearity studies. Notably, CSP1 infected and lysed 21 clinical MDR-C. striatum isolates, demonstrating a wide host range. The phage remained stable in conditions ranging from -40 to 55°C, pH 4 to 12, and in 0.9% NaCl buffer, showing no cytotoxicity. The identification of CSP1, as the first phage targeting clinical C. striatum strains, heralds new possibilities in bacteriophage therapy research, and the development of diagnostic and therapeutic tools against pathogenic bacteria.